Literatura infantil como recurso para promoção de habilidades sociais na prática de professoras da educação infantil - Santos, Juliana Pinto dos (Universidade Federal de São Carlos, 2019)
The childhood is a critical period for social skills learning. In the Early Childhood Education it is important to provide effective and viable resources and strategies for interpersonal development. An alternative is the use of children's literature books as long as the teacher has an adequate repertoire of Educational Social Skills (ESS) to promote the child's interest and to achieve his/her goals. Important initiatives for social-emotional development in the school are developing resources and strategies for intervention as well as investing in continuing teacher training. The objective of this study was: to evaluate the performance of two ESS teachers to tell stories, and to assess the impact of guidance sheets for the use of children's literature to promote social skills in students. The following effects were also assessed: participating in the ESS program; providing the book immediately or in advance at the time of use; repetition or change of book. The teachers evaluated the use of children's literature for the promotion of skills and values of coexistence, and as to the feasibility of using the sheet. Two teachers from Early Childhood Education participated, who were exposed to different conditions of storytelling (book immediately available, access to the guidance sheet, storytelling after PESS, with book and sheet available in advance). The participants had their repertoires of ESS assessed by judges from a filming analysis protocol developed based on the literature and validated by the judges. The teachers' evaluations on the use of children's literature books and the guidance sheet were recorded through questionnaires. The data indicated that there was variation in the performance of the teachers in the different conditions of storytelling (proposed in seven phases). There was a higher frequency and variability of ESS considered relevant for storytelling activities of both participants when they adopted the guidance sheet, in particular, when they first had access to this resource, and only by one participant after the ESS program. Some classes of ESS related to the planning of the activity, such as using complementary resources, organizing the room and performing activity related to the scenario, were presented by the participants only when they had access to the guidance sheet. It discusses the relevance of providing resources and programs for teachers to facilitate effective adoption of different strategies for social-emotional development in the school context. The research design allowed to achieve the objectives, especially the area specialists involvement in the elaboration of the filming analysis protocol as well as judges in the filming analysis. Furthermore, the different conditions of storytelling were important for the control of variables and identification of those more favorable for the teachers’ performance.
Children's literature as a strategy to promote social skills in the practice of pre-school teachers
Keywords: Habilidades sociais; Habilidades sociais educativas; Literatura infantil; Professores; Educação infantil; Social skills; Educational social skills; Children's literature; Teachers; Child education; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::ENSINO E APRENDIZAGEM NA SALA DE AULA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS